2010
DOI: 10.1002/cphc.200900654
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Decay of the Excited Singlet States of Thioxanthone by Internal Conversion and Intersystem Crossing

Abstract: The experimental ultrafast photophysics of thioxanthone in several aprotic organic solvents at room temperature is presented, measured using femtosecond transient absorption together with high‐level ab initio CASPT2 calculations of the singlet‐ and triplet‐state manifolds in the gas phase, including computed state minima and conical intersections, transition energies, oscillator strengths, and spin–orbit coupling terms. The initially populated singlet ππ* state is shown to decay through internal conversion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 44 publications
(65 reference statements)
7
45
0
3
Order By: Relevance
“…Experiments conducted at room temperature in acetonitrile 13 determine comparable IC (5.5 Â 10 9 s À1 ) and ISC (10.6 Â 10 9 s À1 ) rates, thus, supporting our explanation. A recent work by Angulo et al 34 reports the ISC and IC rates in AcN to be 8 Â 10 9 s À1 and 4.1 Â 10 9 s À1 , which are also in good agreement with our results and further support the qualitative picture provided by our calculations. The calculated vibronic spinÀorbit coupling is of the order of 10 7 s À1 .…”
Section: Ground State Geometry and Vertical Excitation Energiessupporting
confidence: 95%
“…Experiments conducted at room temperature in acetonitrile 13 determine comparable IC (5.5 Â 10 9 s À1 ) and ISC (10.6 Â 10 9 s À1 ) rates, thus, supporting our explanation. A recent work by Angulo et al 34 reports the ISC and IC rates in AcN to be 8 Â 10 9 s À1 and 4.1 Â 10 9 s À1 , which are also in good agreement with our results and further support the qualitative picture provided by our calculations. The calculated vibronic spinÀorbit coupling is of the order of 10 7 s À1 .…”
Section: Ground State Geometry and Vertical Excitation Energiessupporting
confidence: 95%
“…Femtosecond (fs) transient absorption spectroscopy has already been applied to TX in cH. 15 In that study, a time constant of B5 ps was observed and ascribed to the depletion of the primary 1 pp* excitation. Based on SE signatures in fs-transient absorption data as well as fs-fluorescence spectroscopy, we will show that in this study 15 a process on the time scale of 100 fs was missed.…”
Section: Introductionmentioning
confidence: 99%
“…15À22 It has attracted considerable attention of both the photophysicists and the photochemists due to its solvatochromic behavior. 15À20, 22,23 The intensity and decay characteristics of the TX fluorescence strongly depend on the nature of the solvent. It has also been found that the tripletÀtriplet (TÀT) absorption maximum is very sensitive to solvent polarity.…”
Section: ' Introductionmentioning
confidence: 99%